Pengaruh Reward Dan Punishment Terhadap Kinerja Karyawan Pada UD.Laris Anda Di Kota Samarinda - Muhammad Rifaldi (Jurnal Administrasi Bisnis Fisipol Unmul, 2021)
Reward and punishment are one of the key to create professional human resources in the company, especially the right reward choosen can increase the quality and quantity of employees to work better and efficient as well as the right punishement choosen can limit employees to make loss for the company to achieve the company’s goal. The purpose of the research is to find and analyze the effect of reward and punishment to employee’s performance at Ud. Laris Anda in Samarinda. Also to find out which variable reacted dominantly towards employee’s performance at UD. Laris Anda in Samarinda. The method for this research is using sample of 35 employees. The sampling’s technique is saturation sampling. Collecting data’s technique is by literature review and observation, interview, and questionares. Analyzing data’s technique is using multiple linear regression. The research found that reward and punishment simultaneously and parcially effected significantly toward employee’s performance at UD. Laris Anda in Samarinda. Writer’s suggestion for the company is to re-supervise the management of human resources in reward and punishment to get professional employee in the future.